Translation Procedures of English Phrasal Verbs into Indonesian on Instagram Captions - Ayu Widiastuti, Ni Made (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
This study aims at comparing the translation procedures of English phrasal verbs used with their definitions and used in sentences into Indonesian found in the captions of an Instagram account’s posts. The translations are done by a Machine Translation (MT) available in the Instagram system as one of its features. The data were taken from the captions of one Instagram account containing the English phrasal verbs as well as their translations into Indonesian provided by its system. The collected data were analyzed qualitatively based on translation procedures. The comparisons of the translation procedures are descriptively reported. The results show that the translation procedures in translating the English phrasal verbs used in sentences are different from the ones used with their definitions, though there are some of them that applied the same procedures, those are borrowing, literal translation, the combination between literal and borrowing, and also equivalent. Borrowing and literal translation procedures and the combination between the two can be considered not appropriate in translating phrasal verbs as the meanings cannot be comprehended literally and from the borrowed term. It can be said that the data sources of English phrasal verbs and their translations in Indonesian language have not been input into the system of the Instagram MT, therefore, the phrasal verbs analyzer failed to match the English and Indonesian phrasal verbs in the process of machine translation